2008
DOI: 10.1111/j.1464-410x.2008.07914.x
|View full text |Cite
|
Sign up to set email alerts
|

Alfuzosin attenuates erectile dysfunction in rats with partial bladder outlet obstruction

Abstract: pressure, and total ICP (area under the curve). Organ-bath studies were performed on corpus cavernosum smooth muscle (CCSM) strips. Nitric oxide synthase (NOS) expression was determined immunohistochemically (IHC) for neuronal (n)NOS and by Western blot analysis for endothelial (e) and inducible (i) NOS protein. RESULTSRats with PBOO showed lower erectile responses than controls. Maximum electrical field stimulation-mediated and endothelium-dependent acetylcholineinduced relaxations and contractile responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 40 publications
5
39
0
Order By: Relevance
“…Thanks to its ability to inhibit smooth muscle contractions, it has been utilized recently for ensuring smooth passage of ureteral calculi. 12,13 Our aim was to investigate whether alfuzosin has protective effects on tubules and kidneys in partial UPO model in order to benefit from its ability to reduces intraluminal pressure in the ureter by selectively blocking a 1a especially in the proximal ureter.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thanks to its ability to inhibit smooth muscle contractions, it has been utilized recently for ensuring smooth passage of ureteral calculi. 12,13 Our aim was to investigate whether alfuzosin has protective effects on tubules and kidneys in partial UPO model in order to benefit from its ability to reduces intraluminal pressure in the ureter by selectively blocking a 1a especially in the proximal ureter.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the average ARI values were similar, this decrease due to the alfuzosin treatment gives rise to the thought that it might be because of an inhibition ensured sympathicomimetically by alfuzosin indirectly, if not directly. 12,13 The study made by Karakus¸et al, it was shown that ARI is fit to be utilized in diagnosing UPO and that enalapril, an ACE inhibitor used on the treatment group, maintains renal blood flow with its effect on the RAA system and decreases ARI values. 30 Glomerulus sclerosis and collapse, proximal and distal tubule dilation, epithelial degeneration, interstitial fibrosis and inflammation, and vascular congestion were reduced statistically in Group UPT by histopathologically (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data are in accordance with our hypothesis about CC-EMG and Eco-Doppler relationship. 25 We did not carry out a reinjection in any patient. We applied the standard dose of 20 mg of Caverject to all the patients.…”
mentioning
confidence: 99%